PENGENALAN RABIES PADA SISWA SD NEGERI MEDOWO 3 MELALUI PROGRAM KOMUNIKASI, INFORMASI, DAN EDUKASI (KIE) - Dameanti, Fidi Nur Aini Eka Puji; luthfiana, Nurul; Sabila, Ahda; Nirmalasari, Na Young; Suseno, Raisa Qurrata A’yun; Erlinda, Tira (Universitas Mataram, 2024)
Rabies is a zoonotic disease that can be transmitted from animals to humans. Rabies remains a global threat, killing around 59,000 people each year, and dogs are still the main source of transmission. The presence of dogs in the community as one of the animals most often infected with rabies is a condition that must always be watched out for, one of which is in the group of children who are at highest risk of being bitten by rabid dogs. Communication, Information, and Education (CIE) is one of the strategies used in the comprehensive approach of the rabies eradication program in Indonesia. Increasing knowledge related to rabies in children can be done through CIE that is packaged attractively without reducing the content and information conveyed. CIE with the theme